Behaviour of tungsten in fusion environment: Damages by hydrogen - Pourcelot, Grégoire; Gervasoni, Juana Luisa (International Journal of Science and Research, 2020)
Fil: Pourcelot, Grégoire. Grenoble Institute of Technology; Francia